ASSOCIATION BETWEEN CARDIOMETABOLIC RISK FACTORS AND COVID-19 SUSCEPTIBILITY, SEVERITY AND MORTALITY: A SYSTEMATIC REVIEWTHE MOST RECENT OUTBREAK OF THE CORONAVIRUS HAS CAUSED WIDESPREAD DEVASTATION ACROSS ALL ASPECTS OF HUMAN EXISTENCE AND HAS ACCELERATE - Totalia, Lely Sustantine (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The most recent outbreak of the coronavirus has caused widespread devastation across all aspects of human existence and has accelerated the spread of the disease throughout the globe. The coronavirus illness that has been identified in 2019 (COVID-19) has been given the name 2019-nCOV. This unique virus is the cause of the COVID-19 disease, which exhibits signs and symptoms that are akin to those of severe acute respiratory syndrome coronavirus 2. (SARS-COV2). Cardiometabolic disease is a group of metabolic abnormalities that increase the risk of type 2 diabetes (T2DM) and cardiovascular diseases (CVDs). These metabolic abnormalities include insulin resistance, hyperglycemia, dyslipidemia, abdominal obesity, and hypertension (HTN). Environmental risk factors include smoking, leading a sedentary lifestyle, eating an unhealthy diet, and being poor. It is also possible to see it as a collection of interconnected pathophysiological abnormalities that take place in the cardiovascular system as well as other metabolic organs, which lead to an increased risk of type 2 diabetes and cardiovascular disease. According to the findings of study, persons who suffer from hypertension, diabetes mellitus type 2, and obesity are strongly associated with the susceptibility of the disease and the severity it manifests in COVID-19 patients. Although high blood pressure, also known as hypertension, is one of the most common cardiovascular comorbidities, it is not yet known whether or not the association between high blood pressure and COVID-19 is independent from advanced age.